Mechanisms of pore formation in hydrogel scaffolds textured by freeze-drying. (August 2019) - Grenier, Jérôme; Duval, Hervé; Barou, Fabrice; Lv, Pin; David, Bertrand; Letourneur, Didier
Graphical abstract: Abstract: Whereas freeze-drying is a widely used method to produce porous hydrogel scaffolds, the mechanisms of pore formation involved in this process remained poorly characterized. To explore this, we focused on a cross-linked polysaccharide-based hydrogel developed for bone tissue engineering. Scaffolds were first swollen in 0.025% NaCl then freeze-dried at low cooling rate, i.e. −0.1 °C min −1, and finally swollen in aqueous solvents of increasing ionic strength. We found that scaffold's porous structure is strongly conditioned by the nucleation of ice. Electron cryo-microscopy of frozen scaffolds demonstrates that each pore results from the growth of one to a few ice grains. Most crystals were formed by secondary nucleation since very few nucleating sites were initially present in each scaffold (0.1 nuclei cm −3  °C −1 ). The polymer chains are rejected in the intergranular space and form a macro-network. Its characteristic length scale coincides with the ice grain size (160  μ m ) and is several orders of magnitude greater than the mesh size (90 nm) of the cross-linked network. After sublimation, the ice grains are replaced by macro-pores of 280 μ m mean size and the resulting dry structure is highly porous, i.e. 93%, as measured by high-resolution X-ray tomography. In the swollen state, the scaffold mean pore size decreases in aqueous solvent of increasing ionic strength (120 µm in 0.025% NaCl and 54 µm in DBPS) but the porosity remains the same, i.e. 29% regardless of the solvent. Finally, cell seeding of dried scaffolds demonstrates that the pores are adequately interconnected to allow homogenous cell distribution. Statement of Significance: The fabrication of hydrogel scaffolds is an important research area in tissue engineering. Hydrogels are textured to provide a 3D-framework that is favorable for cell proliferation and/or differentiation. Optimum hydrogel pore size depends on its biological application. Producing porous hydrogels is commonly achieved through freeze-drying. However, the mechanisms of pore formation remain to be fully understood. We carefully analyzed scaffolds of a cross-linked polysaccharide-based hydrogel developed for bone tissue engineering, using state-of-the-art microscopic techniques. Our experimental results evidenced the shaping of hydrogel during the freezing step, through a specific ice-templating mechanism. These findings will guide the strategies for controlling the porous structure of hydrogel scaffolds.